The Influence of The Internet As A Source of Online Literature and The Level of Student Plagiarism - Sukri, Muhammad; Damopolii, Muljono; Nursalam, Nursalam (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
This study aims to describe the level of intensity of internet use as a provider of online literature and the level of plagiarism committed by students. In addition, the significance of the influence of the intensity of internet use as a provider of online literature on the level of student plagiarism is also seen here. The population in this study was all students of the Department of Islamic Religious Education, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar, for the 2019/2020 academic year, totaling 312 people. Using stratified random sampling, 31 people were selected as the sample. Data collection was carried out using a questionnaire and analyzed with descriptive and inferential statistics. The results of this study indicate that first, the measure of the intensity level of internet use as a provider of online literature is included in the moderate qualification, namely the average (mean) of 32.65. Second, the measure of the level of plagiarism among students of the Department of Islamic Religious Education, the Faculty of Tarbiyah, and Teacher Training is included in the moderate qualification, namely the average (mean) of 38.39. Therefore, this article concludes that there is a significant influence between the intensity of internet use as a provider of online literature and the level of plagiarism.